HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAK TAKRAW PADA TIM SEPAK TAKRAW PPLM PUTRI PROVINSI RIAU - Saputra, Deden Tri; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is still weak football skills sila Games Sepak Takraw In sepak takraw team PPLM daughter Riau Province. This study is correlational is to determine the relationship of a variable associated with other variables. The population in this study is the athletes who participated in the exercise amounted to 4 people. While sampling in this study using total sampling technique or saturated samples, amounting to 4 people. To obtain research data conducted tests and measurements, the eye and foot coordination tests and test football sila. Prior to the analysis first tested with test data normality Lilefors. Analysis of the data using the formula and continued with Product Moment Correlation with Distribution Test Signifikasni. Based on the research that has been described in the previous chapter can be argued conclusion there is no significant relationship between the eye and foot coordination with football skills sila as obtained ro = 0.905 rtab (α = 0.05) = 0.997 Turns ro <rtab consequently Ha rejected.Key Words : Eye coordination and foot, football skills sila